LEG ULCERS – GOOD RESPONSE TO TREATMENT WITH COLLAGEN, OXIDIZED REGENERATED CELLULOSE AND SILVER MATRIX - Santos, Guida; Sousa, Lourdes; João, Alexandre (Journal of the Portuguese Society of Dermatology and Venereology, 2014)
A greater understanding of the pathophysiology of leg ulcers has allowed the development of new therapeutic modalities. Matrices as collagen and oxidized regenerated cellulose may, by binding to proteases, lower matrix degradation, protection and stabilization of growth factors, promoting the ulcer’s healing. A 72-year-old male patient with metabolic syndrome and venous insufficiency, peripheral arterial disease, presented recalcitrant extensive and long-term ulcers, cured with dressings matrix collagen, oxidized regenerated cellulose and silver.